Efficient Broadband Triplet–Triplet Annihilation‐Assisted Photon Upconversion at Subsolar Irradiance in Fully Organic Systems. (25th August 2015) - Monguzzi, Angelo; Borisov, Sergey M.; Pedrini, Jacopo; Klimant, Ingo; Salvalaggio, Mario; Biagini, Paolo; Melchiorre, Fabio; Lelii, Camilla; Meinardi, Francesco
Abstract : The latest trend in solar cell technology is to develop photon managing processes that adapt the solar emission to the spectral range at which the devices show the largest intrinsic efficiency. Triplet–triplet annihilation‐assisted photon upconversion (sTTA‐UC) is currently the most promising process to blue‐shift sub‐bandgap photons at solar irradiance, even if the narrow absorption band of the employed chromophores limits its application. In this work, we demonstrate how to obtain broadband sTTA‐UC at sub‐solar irradiance, by enhancing the system's light‐harvesting ability by way of an ad‐hoc synthesized family of chromophores with complementary absorption properties. The overall absorptance is boosted, thus doubling the number of upconverted photons and significantly reducing the irradiance required to achieve the maximum upconversion yield. An outstanding yield of ≈10% is obtained under broadband air mass (AM) 1.5 conditions, which allows a DSSC device to operate by exploiting exclusively sub‐bandgap photons. Abstract : Broadband triplet–triplet annihilation‐assisted photon upconversion is demonstrated at subsolar irradiance by the simultaneous use of several light harvesters. An unprecedented yield of 10% is obtained under air mass (AM) 1.5 conditions in a fully organic system, which allows a dye‐sensitized solar cell device to operate by exploiting exclusively sub‐bandgap photons.